2017
DOI: 10.1308/rcsbull.2017.28
|View full text |Cite
|
Sign up to set email alerts
|

Variation in CCG policies for the treatment of carpal tunnel syndrome

Abstract: Are CTS patients receiving equal standards of care across the country?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Despite local clinical commissioning policies that advocate conservative treatment first, the proportion of participants having a steroid injection in the first 6 months was only 9%, which is in contrast to 52% proceeding directly to surgery. This may be due, in part, to some patients having had symptoms for some time or having receiving a steroid injection prior to referral for NCS and enrolment in our study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Despite local clinical commissioning policies that advocate conservative treatment first, the proportion of participants having a steroid injection in the first 6 months was only 9%, which is in contrast to 52% proceeding directly to surgery. This may be due, in part, to some patients having had symptoms for some time or having receiving a steroid injection prior to referral for NCS and enrolment in our study.…”
Section: Discussionmentioning
confidence: 94%
“…13 Some healthcare systems use restrictive policies in which surgery is offered only in cases in which symptoms persist for more than 3 months after initial conservative therapy or in which the patient suffers from significant functional impairment or has a neurological deficit. 14 Several studies have explored a range of prognostic factors for outcome from surgical and conservative treatments. [15][16][17][18] However, these studies were limited by small sample sizes, a poor ratio of events to number of factors being studied resulting in overfitting, a restricted range of variables, or the use of univariable analysis rather than multivariable models or were retrospective.…”
mentioning
confidence: 99%
“… 27 In the UK, CTR has been labeled by some Clinical Commissioning Groups (member organizations who determine how National Health Service (NHS) funds are spent in a particular locality) as a “procedure of limited clinical value” leading to variable patient access to the procedure. 28 The Royal College of Surgeons expressed their concern on the potential impact on patient health and well-being. 29…”
Section: Introductionmentioning
confidence: 99%
“…There has been much debate over the value of NCS in the diagnosis of CTS, 1 22–24 and in the UK not all patients have NCS. 7 Several studies have examined the association of self-reported symptoms and function with objective severity from electrodiagnostic findings. Most have used simple correlations with the exception of Chan et al .…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of policies from 175 CCGs in England highlighted that these were highly variable in terms of criteria for defining severity, the necessity for nerve conduction studies (NCS) and duration of non-operative treatment before referral for surgery is allowed. 7 Controversy continues over the best management of CTS at different stages. More recent research on CTS has highlighted the role of psychological factors such as anxiety, depression and patient’s health beliefs in how patients perceive their symptoms, their impact on function and the outcome from treatment.…”
Section: Introductionmentioning
confidence: 99%